Rosemary extract primes cultivar-dependent defense responses in potato against pathogen attack - Martin, Ana Paula (2026)
Potato (Solanum tuberosum L.) is a major global food crop increasingly threatened by viral and oomycete pathogens, such as potato virus X (PVX) and Phytophthora infestans, whose impact is exacerbated under changing environmental conditions. Although priming strategies offer a sustainable approach to enhance disease resistance, it remains unclear how cultivar-specific metabolic states influence priming efficiency. Infection responses to PVX (strain ROTH1) and a P. infestans isolate were evaluated in four commercial cultivars. Cultivar-dependent differences were observed: Innovator exhibited higher resistance, Kennebec and Spunta greater susceptibility, and Frital-INTA was resistant to PVX ROTH1 but susceptible to P. infestans. 1H NMR metabolomics combined with defense gene expression analysis under non-inoculated conditions revealed distinct cultivar-specific signatures. Resistant and susceptible cultivars segregated into separate clusters, identifying metabolites associated with constitutive defense states. These results indicate that basal metabolic configuration contributes to differential pathogen susceptibility and may influence responsiveness to priming. Spunta, due to its broad cultivation and susceptibility, was selected to assess aqueous rosemary extract (ARE)-mediated priming. ARE treatment reduced PVX ROTH1 accumulation by ~ 70% and decreased P. infestans lesion size by ~ 30%, demonstrating that it enhances potato immunity by integrating both constitutive and inducible defense mechanisms.